Konflik Penolakan Ritual Doa Leluhur Paguyuban Padma Buana di Pedukuhan Mangir Bantul, Yogyakarta - Setyo Boedi Oetomo (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
The people of Yogyakarta are known for their tolerance, where people of different religions can coexist peacefully especially with Javanese traditions. But in Mangir, a village in Bantul, Yogyakarta, in November 12, 2019, there was a case of local residents rejecting the procession of ancestral prayer rituals by the Paguyuban Padma Buana (PPB) who claims to be followers of Javanese Hinduism. This study aimed at disclosing the elements and roots of conflict from the Mangir community's rejection towards Paguyuban Padma Buana. As a case study, it used conflict analysis approach through timeline and factor analysis techniques. The results showed that the open conflict between the two groups has occurred since 2012 with the main issue of syncretic ritual practices of Hinduism, Buddhism, and Kejawen (Javanism) that involve people from various religions. In addition, the Maha Lingga Padma Buana Temple as a place of whorship and rituals has also the license problems. Reconciliation was carried out between residents with the Padma Buana followers in 2015. Unfortunately it was violated by the Paguyuban Padma Buana and became a trigger of conflict back in 2019. The cause of this conflict is multiple factors, all of which are interrelated. However, the root cause of the problem among Mangir people is mostly related to traditional revivalism and the distribution of cultural tourism management authorities. This conflict makes them polarized and vulnerable to interests that can create the village atmosphere worse